Muscle mass change using linear measurement analysis after nephrectomy for pT3 and pT4 renal cell carcinoma is associated with mortality. Issue 2 (15th June 2022) - Medline, Alexandra; Midenberg, Eric; Patil, Dattatraya; Evans, Sean; Vettikattu, Nikhil; Kamal, Fatima; Ogan, Kenneth; Psutka, Sarah P.; Bilen, Mehmet Asim; Master, Viraj A.
Abstract: Background: Preoperative skeletal muscle deficiency is an established risk factor for poor survival outcomes in patients with renal cell carcinoma (RCC). However, given the dynamic nature of skeletal muscle associated with malignancy, there is a need to evaluate the prognostic benefit of muscle area change from the preoperative to postoperative period. We hypothesize that an improvement in muscle area following nephrectomy, measured by linear segmentation of L3 psoas and paraspinal musculature, is associated with improvement in overall survival (OS) and cancer specific survival (CSS) for patients with pT3 and pT4 RCC. Methods: We retrospectively analysed 270 pT3 and pT4 RCC patients who underwent nephrectomy from March 2004 to February 2020 with available preoperative and postoperative axial CT or MRI studies segmented at the L3 vertebrae. The majority were N0 (79%) and M0 (68%). Psoas and paraspinal muscles were measured bilaterally using a validated digital ruler tool. Total muscle area (TMA) was calculated by aggregating the area of all four muscles and total muscle area index (TMI) by dividing the TMA by height squared (m 2 ). The prognostic value of postoperative muscle improvement, defined as any increase in muscle area index, was analysed using Kaplan–Meier and Cox proportional stepwise hazard models. Results: Median time between preoperative scans and surgery was approximately 22 days and between surgery and postoperative scans 172 days. One hundred twenty‐one patients (44.8%) had an increase in total muscle area index post‐nephrectomy (IQR = 33.4; P ≤ 0.0001). On Kaplan–Meier analysis, postoperative improvement in TMI was associated with decreased odds of mortality ( P = 0.0024) with a median follow‐up of 38.6 months. In a multivariable Cox regression analysis, improvement of TMI was associated with increased OS (HR = 0.52, 95% CI 0.35–0.78, P < 0.001) and increased CSS (HR = 0.55, 95% CI 0.32–0.94, P = 0.030). A 5% or more improvement in TMI was also associated with increased OS (HR = 0.53, 95% CI 0.34–0.84, P = 0.006) and increased CSS (HR = 0.46, 95% CI 0.24–0.86, P = 0.015). Conclusions: Any improvement in TMI between preoperative and initial postoperative imaging after nephrectomy was associated with increased OS and CSS in patients with pT3 and pT4 RCC. Perioperative linear segmentation is an efficient tool that may improve current prognostication methods and can be performed on any imaging software platform.